A new species of Drepanocnemis (Diptera, Muscidae) from Andes in Peru, with an updated phylogenetic analysis of species - Lucas Roberto Pereira Gomes; Márcia Souto Couri; Claudio José Barros de Carvalho (Revista Brasileira de Entomologia)
ABSTRACT Drepanocnemis Stein (Diptera, Muscidae) is a small genus of flies that occur in high altitudes in the Colombian Andes, Ecuador, Peru and Bolivia. Herein we describe Drepanocnemis aurifrons sp. nov. from Cuzco, Peru, which is found from high (2904 m) to lower altitudes (707 m). An updated phylogeny, key to species and map of species’ distributions are provided, together with images and illustrations of the male and the female terminalia.